Tokyo Rose -- Zero hour : a Japanese American woman's persecution and ultimate redemption after World War II - Frattino, Andre R., 1984- (Tuttle Publishing, 2022)
"Tells the true story of Iva Toguri, a Japanese American woman who was visiting relatives in Tokyo shortly before the attack on Pearl Harbor. Trapped in Japan, Iva was pressed to renounce her American citizenship, but refused. As war raged across the Pacific, she took a job with Radio Tokyo-where she was forced to host "Zero Hour," a propaganda show aimed at demoralizing American troops-in the role of Tokyo Rose, the "Siren of the Pacific.""--Publisher's description.